An in vitro lung model to assess true shunt fraction by multiple inert gas elimination. - Balamurugan Varadarajan; Andreas Vogt; Volker Hartwich; Rakesh Vasireddy; Jolanda Consiglio; Beate Hugi-Mayr; Balthasar Eberle (PLoS ONE)
The Multiple Inert Gas Elimination Technique, based on Micropore Membrane Inlet Mass Spectrometry, (MMIMS-MIGET) has been designed as a rapid and direct method to assess the full range of ventilation-to-perfusion (V/Q) ratios. MMIMS-MIGET distributions have not been assessed in an experimental setup with predefined V/Q-distributions. We aimed (I) to construct a novel in vitro lung model (IVLM) for the simulation of predefined V/Q distributions with five gas exchange compartments and (II) to correlate shunt fractions derived from MMIMS-MIGET with preset reference shunt values of the IVLM. Five hollow-fiber membrane oxygenators switched in parallel within a closed extracorporeal oxygenation circuit were ventilated with sweep gas (V) and perfused with human red cell suspension or saline (Q). Inert gas solution was infused into the perfusion circuit of the gas exchange assembly. Sweep gas flow (V) was kept constant and reference shunt fractions (IVLM-S) were established by bypassing one or more oxygenators with perfusate flow (Q). The derived shunt fractions (MM-S) were determined using MIGET by MMIMS from the retention data. Shunt derived by MMIMS-MIGET correlated well with preset reference shunt fractions. The in vitro lung model is a convenient system for the setup of predefined true shunt fractions in validation of MMIMS-MIGET.